La Crónica abreviada de don Juan Manuel en la historiografía post-alfonsí - Salgado Loureiro, José Ángel (Historiografías, 2019)
The study of the Crónica abreviada has been traditionally linked to the criticism of its principal source, the Estoria de España by Alfonso X. In the analysis and interpretation of the work, the experts have focused mostly upon textual or literary aspects. Regarding the figure of Don Juan Manuel as an author, two main lines of study can be identified. The one that has related him to the noble post-alfonsí chronicler, detractor of the Castilian royal ideology, and the other focused upon the use of the authorial image of the “Learned King”. In this article we shall tackle the textual and ideological rationale of the Crónica abreviada within the post-Alphonsine chronicle. To that purpose, we present an historiographic approach to understand the reality of Don Juan Manuel as a post-Alphonsine chronicler in the early 14th century.